Enhancing Studens’ Active Involvement in Reading Learning and Reading Comprehension Based On the Reading Text-Based Situational Needs and Interest - Yudi Rahmatullah (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2015)
The research aims to enhance the students’ active involvement in reading learning and reading comprehension based on the reading text-based situational needs and interest. The research is conducted in SMAN Cahaya Madani Banten Boarding school (CMBBS) at the twelfth grade students. The data is collected from interview, observation and questionnaire. The data is analyzed from the students’ active involvement in reading learning and the students’ reading comprehension based on the reading text-based situational needs and interest. From the two types of the reading texts, the researcher sees the students’ active involvement in each group and amongst the group in reading learning and the students’ reading comprehension on the reading text-based situational needs and interest. The findings of the research are the students’ active involvement in reading learning using the reading text-based situational needs is well-enhanced and the students’ reading comprehension using the reading text-based situational needs is also well-enhanced. The students involved themselves actively in reading learning on the reading text-based situational needs in each group and amongst the groups and the students comprehended the reading text-based situational needs well. The conclusions of the research are the reading texts-based situational needs can enhance the students’ active involvement in reading learning and the students’ reading comprehension on the reading texts.